EVALUATING THE ELECTRONIC-BASED GOVERNMENT SYSTEM (SPBE) POLICY IN ENHANCING PUBLIC SERVICE QUALITY: A CASE STUDY OF IMPLEMENTATION IN INDONESIAN LOCAL GOVERNMENT - Lydia Tengker; Margareth I R. Rantung; Handri Rumengan (PT. Radja Intercontinental Publishing, 2026)
Indonesian local governments and analyze its impact on improving public service quality. SPBE, mandated through Presidential Regulation Number 95 of 2018, represents Indonesia's digital government transformation framework to achieve efficient, transparent, and accountable governance. Design/Methodology/Approach – This research employs a qualitative approach with a case study method on SPBE implementation across several local governments in Indonesia. The evaluation utilizes the maturity level model based on Ministry of PAN-RB Regulation Number 59 of 2020, encompassing four main domains: internal SPBE policies, SPBE governance, SPBE management, and SPBE services. Data were collected through in-depth interviews with civil apparatus managing SPBE systems, direct observation of implemented systems, and document analysis of SPBE evaluation reports. Findings – The results indicate that SPBE implementation has significantly contributed to improved efficiency, transparency, and accessibility of public services. However, disparities in SPBE index achievement across regions were identified, with key determining factors including: (1) system standardization and interoperability, (2) clarity of operational procedures, (3) technology harmonization, and (4) institutional collaboration. Implementation standardization proved to be the most critical factor determining SPBE success in enhancing service quality. The national SPBE index reached 3.12 in 2024 (good category), exceeding the 2020-2024 National Medium-Term Development Plan target of 2.60 . Research Limitations/Implications – This study is limited to several local governments and does not comprehensively represent all regions in Indonesia. Future research could expand the sample and employ quantitative approaches to measure SPBE's direct impact on citizen satisfaction. Practical Implications – The findings provide strategic recommendations for local governments to enhance SPBE implementation through strengthening change management, improving human resource capacity, and developing adequate technological infrastructure . Originality/Value – This research contributes to the e-government evaluation literature by identifying critical success factors in SPBE implementation within Indonesia's decentralized governance context, offering insights for policymakers and practitioners in developing countries undergoing similar digital transformation initiatives.